1992
DOI: 10.1007/bf00157007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy of the vitreous body in rhesus monkeys and man

Abstract: In the isolated unfixed vitreous body a structural organization can be visualized by slitlamp microscopy or by an ink-injection technique. We discuss the observations on human and rhesus monkey (Macaca mulatta) vitreous bodies using the ink-injection technique. Advantages and disadvantages of this method compared with slitlamp microscopy are described. Eventual functional implications of vitreal organization are mentioned briefly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Most of the soluble protein present in the vitreous is derived from plasma, and albumin and immunoglobulins represent ~80% of the protein content of the vitreous ( Bishop 2014 ). Studies utilizing fixation and dye injection demonstrate similarity in vitreous structure between human, non-human primate, and rabbit, and likely other species ( Los 2008 ; Worst and Los 1992 ). Therefore, a generalized presentation of the vitreous is provided and pertains to all species.…”
Section: Nonproliferative and Proliferative Lesions Of The Rat Andmentioning
confidence: 99%
“…Most of the soluble protein present in the vitreous is derived from plasma, and albumin and immunoglobulins represent ~80% of the protein content of the vitreous ( Bishop 2014 ). Studies utilizing fixation and dye injection demonstrate similarity in vitreous structure between human, non-human primate, and rabbit, and likely other species ( Los 2008 ; Worst and Los 1992 ). Therefore, a generalized presentation of the vitreous is provided and pertains to all species.…”
Section: Nonproliferative and Proliferative Lesions Of The Rat Andmentioning
confidence: 99%
“…Contrary to the general belief, we assume that TA may accumulate on the anterior wall of the BPM, rather than on the posterior surface. The accumulation of TA on the BPM surface might actually occur, presumably because of the feathery texture of the surface, which Worst previously reported [12].…”
Section: Discussionmentioning
confidence: 95%
“…Two pioneers of vitreous anatomy, Dr. Jan Worst and Dr. Shoji Kishi, explored the enigmatic structure of the premacular vitreous using different methods [2, 3]. Worst first described the BPM as a liquid-filled sac-like space of the vitreous overlying the macula, and found the BMP connected to the cisternal system, which occupied a significant portion of the vitreous, by injecting India ink into postmortem eyes [12, 13]. Kishi et al observed the vitreous of enucleated eyes by staining with fluorescein, and found that a gel-free region was present in the vitreous anterior to the macula, which they termed PPVP [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations